Symbolic interaction and new social media - Johns, Mark D.; Chen, Shing-Ling; Terlip, Laura A. (Studies in symbolic interaction., 2014)
This volume builds on and expands the existing symbolic interactionist perspective to include the study of social interaction made possible by the use of new social media.